Population development in Czechoslovakia in 1982 - Ales, M (Demosta, 1983)
Population trends in Czechoslovakia in 1982 are reviewed. The growing impact of some irregularities in age distribution, such as the decline in the number of women aged 20 to 24, on fertility and mortality is noted.
Keywords: mortalita; Demographic Factors; vyspělé země; Age Distribution; fertilita; Europe; Europe, Eastern; Czechoslovakia; Evropa; Československo; Population Characteristics; Developed Countries; věkové faktory; východní Evropa; Demographic Impact; populace; věkové rozložení; Mortality; populační dynamika; Demography; Fertility; demografie; Population; Age Factors; populační charakteristiky; Population Dynamics; Eastern Europe